PRINSIP LANDASAN PENDIDIKAN ISLAM DALAM PERSPEKTIF FIQIH - raihanaaulia; Chanifudin (EL-TA’DIB: Journal of Islamic Education, 2025)
Islamic education, when viewed through the perspective of fiqh, emphasizes not only the transfer of knowledge but also the internalization of Sharia-based values derived from the Qur’an and Sunnah. This study addresses the current challenges in Islamic education, where practices often focus on cognitive and ritualistic aspects without adequately integrating fiqh as a normative-ethical foundation. Using a qualitative literature review approach, this research explores the principles of Islamic educational values grounded in fiqh, highlighting their ethical, cognitive, and moral dimensions. The findings indicate that fiqh serves as a comprehensive framework for shaping students’ character, promoting moral excellence, social responsibility, and the pursuit of both worldly and spiritual well-being. The study also demonstrates that embedding fiqh principles into curricula enhances moderation, inclusivity, and responsiveness to contemporary societal challenges. By positioning fiqh as both a source of knowledge and an ethical foundation, Islamic education can function as a transformative vehicle, preparing students to act constructively and responsibly within modern society. This research contributes conceptually by offering a systematic mapping of fiqh-based educational principles, providing guidance for curriculum development, pedagogical strategies, and character formation in contemporary Islamic education.